Verification of the Hadiths and Narrations in the Interpretation of Sheikh Muhammad al-Khal (Part One as a Model) - Ahmed, Asst. Prof. Dr. Aso Reda (Sulaimani Journal for Humanities, 2023)
The research extracts the hadiths and narrations mentioned in the first part of Sheikh Muhammad Al-Khal’s interpretation in a scientific manner, by referring them to their sources in approved books and indicating their degree, relying on the statements of scholars of the subject in this field, in the hope that the extraction of the hadiths and narrations mentioned in the rest of the parts of the interpretation will be completed.